Analisa Undang-Undang 26 Tahun 2007 terhadap Penyediaan Ruang Terbuka Hijau Berdasarkan Prinsip Good Environmental Governance Di Kota Yogyakarta - Berliant Pratiwi; Eko Priyo Purnomo (Wajah Hukum, 2021)
Yogyakarta as one of the cities that has a rapidly growing population requires an adequate amount of space. Based on Law No. 23/2007 and Yogyakarta City Regulation No. 10/2010, there is an obligation for the local government to provide open space for urban areas, which is 30% of the total area of the city concerned. Yogyakarta itself until 2019 only has 19% of the availability of green open space locations. This research uses the Normative Juridical method which will examine legal issues with a concept and legal principles. In this research, the writer raises the problem regarding the application of the principles of good environmental governance in urban spatial management which is analyzed using the Belbase Theory. The purpose of this study is to analyze the application of the principles of good environmental governance in the management of green open space in the city of Yogyakarta and to find out the potential of the city of Yogyakarta in providing green open space locations. The results of this study are that the achievement of green open spaces that we aspire to. in laws and regulations can be applied through the principles of good environmental governance. However, it must be considered beforehand regarding the problems that must be faced by local governments so that the implementation of the principles of good environmental governance can be optimally applied.